Residual Phytotoxicity Effects of Paraquat, Glyphosate and Glufosinate-Ammonium Herbicides in Soils from Field-Treated Plots - Wibawa, Wahyu; Mohamad, Rosli; Puteh, Adam; Omar, Dzolkhifli; Juraimi, Abdul Shukor; Abdullah, Sheikh Awadz (2009)
Soil residual phytotoxicity of commonly used herbicides in plantation crops in Malaysia were investigated through bioassay. Paraquat (GramoxoneR) and glufosinate-ammonium (BastaR) at 200, 400, 600 and 800 g a.i. ha-1, and glyphosate (Round-upR) at 400, 800, 1200 and 1600 g a.i. ha-1 were applied to field plots of 5 x 20 m2. Cucumber and corn were used in the bioassay to test the residual effect of herbicides in the soil of the treated plots. Soil, sampled at 1 day after treatment (DAT) and until 2 weeks (WAT) later, did not affect the seed germination and seedling development of cucumber and corn. Recommended rates, paraquat (400-600 g a.i. ha-1), glufosinate-ammonium (500 g a.i.ha-1) and glyphosate (1000 g a.i. ha-1) applied to field to control weeds in oil palm plantation, therefore leave no phytotoxic residue in the soil.